Android Mobile Malware Surveillance Exploitation Via Call Logs: Proof of Concept - Madihah Mohd Saudi; Farida Hazwani Mohd Ridzuan; Nurlida Basir; Nur Fatin Nabila Mohd Rafei Heng; Sakinah Ali Pitchay; Ahmad, IN (IEEE, 2024)
The invention of smartphone have made life easier as it is capable of providing important functions used in user's daily life. While different operating system (OS) platform was built for smartphone, Android has become one of the most popular choice. Nonetheless, it is also the most targeted platform for mobile malware attack causing financial loss to the victims. Therefore, in this research, the exploitation on system calls in Android OS platform caused by mobile malware that could lead to financial loss were examined. The experiment was conducted in a controlled lab environment using open source tools by implementing dynamic analysis on 1260 datasets from the Android Malware Genome Project. Based on the experiment conducted, a new system call classification to exploit call logs for mobile attacks has been developed using Covering Algorithm. This new system call classification can be used as a reference for other researcher in the same field to secure against mobile malware attacks by exploiting call logs. In the future, this new system call classification could be used as a basis to develop a new model to detect mobile attacks exploitation via call logs.